Retraction: Selective uptake of uranium, plutonium and americium on hydrogen titanate nanotubes. Issue 115 (7th December 2016) - Banerjee, Chayan; Dudwadkar, Nilesh; Chandra Tripathi, Subhash; Gandhi, Pritam Maniklal; Kaushik, Chetan Prakash; Chaterjee, Sriparna; Ayyub, Pushan; Tyagi, Avesh Kumar
Abstract : Retraction of 'Selective Uptake of Uranium, Plutonium and Americium on Hydrogen Titanate Nanotubes' by Chayan Banerjee et al., RSC Adv., 2014, DOI: 10.1039/c3ra42548g.